2016
DOI: 10.1159/000445210
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Sensitivity after Pars Plana Vitrectomy: Comparison between Macula-On and Macula-Off Rhegmatogenous Retinal Detachment

Abstract: Purpose: To evaluate the contrast sensitivity (CS) of eyes successfully repaired by vitrectomy for rhegmatogenous retinal detachment (RRD) with or without preoperative macular involvement. Methods: In this retrospective, consecutive, interventional case series, 109 eyes received primary vitrectomy for RRD, of which 36 with at least 12 months of follow-up and a best-corrected visual acuity (BCVA) ≥1 at 12 months postoperatively were investigated. The main outcome measurements were BCVA and CS at 12 months posto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…27 The reduced thickness does not worsen throughout follow-up at 1 or more than 2 years. It could be the consequence of macular detachment as observed in detachments of macula-off retina, which have a worse visual prognosis than macula-on retina, 28,29 which appears correlated to whether or not there is an intact EZ line post-operatively. 30 However, we observed no alterations in total macular retinal thickness at either 1 or 2+ years post-injection, in contrast to the findings of both Bainbridge et al 12 and Jacobson et al, 13 who attributed the progressive decrease in retinal thickness to the pursuit of retinal degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…27 The reduced thickness does not worsen throughout follow-up at 1 or more than 2 years. It could be the consequence of macular detachment as observed in detachments of macula-off retina, which have a worse visual prognosis than macula-on retina, 28,29 which appears correlated to whether or not there is an intact EZ line post-operatively. 30 However, we observed no alterations in total macular retinal thickness at either 1 or 2+ years post-injection, in contrast to the findings of both Bainbridge et al 12 and Jacobson et al, 13 who attributed the progressive decrease in retinal thickness to the pursuit of retinal degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that CS worsened after ocular surgeries, such as laser in situ keratomileusis and macula-on rhegmatogenous retinal detachment, which might be due to decreased central VA after surgery 16 , 21 , 22 . However, even patients with good postoperative VA have decreased CS, and this could possibly be due to factors other than VA such as surgical stress and visual discomfort 23 . CS is temporarily decreased after refractive surgeries but is recovered after 3 months 16 .…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38] Using the 25-item National Eye Institute Visual Function Questionnaire in patients with RRD, 39 Okamoto et al reported vision-related quality of life to be significantly correlated with postoperative CS measured by preprinted letter charts, yet no correlation was found between vision-related quality of life and postoperative VA. 40 Several previous reports have shown reduced CS in patients with RRD using preprinted letter charts. [41][42][43] Despite measuring CS using methods with poor range and resolution for sampling target contrast and frequency [28][29][30] and poor test-retest reliability, 29,31,32 those reports demonstrated the detrimental effect of RD on CS.…”
Section: Discussionmentioning
confidence: 99%
“…43 Kawamura et al demonstrated lower CS in 36 macula-off RRD eyes with a postoperative BCVA of greater than 1.0 compared with macula-on RRD eyes following surgery. 42 The latter group used a Takagi glare tester CGT-2000 to measure CS, which has been shown to have relatively poor accuracy and repeatability. 44 In clinical practice, a visual function metric more sensitive to subtle changes than VA would be particularly valuable in detecting subtle subjective visual impairment noted by the patient and subsequently better guide our clinical judgment on initiating and evaluating our therapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%